Hubungan Intensitas Membaca Al-Quran terhadap Tingkat Kecemasan Mahasiswa Departemen Psikologi UNP - Zahwa Saviola Ramadhini (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
University students frequently face various academic demands, such as coursework, research, field practice, and examinations. These pressures may lead to psychological stress that can trigger anxiety. If not properly managed, anxiety can negatively affect academic performance, social interactions, and students’ psychological well-being. The aim of this study was to examine the relationship between the intensity of Qur’an recitation and the level of anxiety among students. This research employed a quantitative descriptive design involving 103 students from the Department of Psychology, Padang State University as participants. The sampling technique used was nonprobability sampling with a purposive sampling approach. The instruments consisted of the Qur’an Reading Intensity Scale adapted from Pradika (2014) with a reliability coefficient of 0.721, and the Zung Self-Rating Anxiety Scale with a reliability coefficient of 0.829. Data were analyzed using Pearson’s product-moment correlation test. The findings revealed a significant negative correlation between the intensity of Qur’an recitation and students’ anxiety levels (r = -0.801; p = 0.000 < 0.05). This indicates that the more frequently students read the Qur’an, the lower their anxiety levels, and vice versa. Categorization results further showed that most students had a high intensity of Qur’an recitation (42.7%) and experienced low to moderate levels of anxiety (78.7%). These results reinforce previous studies suggesting that spiritual practices such as Qur’an recitation can serve as an effective spiritual coping strategy to foster tranquility, regulate emotions, and strengthen resilience in facing academic stressors. Therefore, Qur’an recitation can be recommended as a complementary approach to maintaining students’ mental health in higher education settings.